Rationale and methods of the MOVI-da10! Study -a cluster-randomized controlled trial of the impact of classroom-based physical activity programs on children's adiposity, cognition and motor competence - Mairena Sánchez-López; Abel Ruiz-Hermosa; Andrés Redondo-Tébar; María Eugenia Visier-Alfonso; Estela Jimenez-López; Maria Martínez-Andres; Montse Solera-Martínez; Alba Soriano-Cano; Vicente Martínez-Vizcaíno; on behalf of MOVI group (BMC, 2019)
Abstract Background Although physical activity (PA) integrated in schools' classrooms have shown a positive effect on children's behaviors, its effectiveness on cognitive functions, PA levels and other health variables remains unclear. This article outlines the rationale and methods of two classroom-based PA interventions (MOVI-da10!) on improving adiposity, executive function and motor competence in preschool children. Methods A three-arm cluster-randomized controlled trial (RCT) was carried out including eight schools (rural and urban areas) from Cuenca province, Spain. The schools were allocated to one of three groups: MOVI-da10-Enriched! intervention (n = 3), MOVI-da10-Standard! intervention, (n = 2), and the control group (n = 3). Around 900 children aged 4 to 6 years old were assesed at baseline (September 2017) and at the end (June 2018) of the intervention. The primary outcomes were changes in body fat by bioimpedance, executive function and motor competence. During a school year (from October 2017 to May 2018), children belonging to the MOVI-da10-Enriched! group performed enriched PA integrated into the academic curriculum including two active breaks lasting 10 min, 5 days/week. The children belonging to the MOVI-da10-Standard! group performed PA breaks (with low cognitive demand, where curricular contents were not reinforced) including two active breaks lasting 10 min, 5 days/week. In the control group, regular PA continued. Discussion To our knowledge, MOVI-da10! is the first RCT to examine the effectiveness of two programs (enriched PA integrated into the academic curriculum and PA breaks only) versus a control group on improving adiposity, executive function and motor competence in preschool children. Trial registration NCT03236363 (clinicaltrials.gov), 31st July 2017.